PENGEMBANGAN MEDIA KOMIK BERBASIS PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN LITERASI SAINS UNTUK SISWA KELAS VIII SMP - Achmad, Naza Meilani; Sari, Mella Mutika; Hafizah, Ellyna (Physics and Science Education Journal (PSEJ), 2025)
This research is a development of comic media based on Project Based Learning (PjBL) which is motivated by the lack of variation of learning media in improving students' scientific literacy. This study aims to determine the validity, practicality, and effectiveness of comic learning media based on Project Based Learning (PjBL) on the digestive system sub-material. This research and development uses the R & D development model with ADDIE research procedures. Data analysis techniques in this study include analysis of the validity of comic media before the media is used in learning with a validity sheet instrument from an expert validator's assessment, analysis of the practicality of comic media related to students' views on comic media used in learning through student response questionnaire instruments, and analysis of the effectiveness of comic media related to improving students' scientific literacy results from the scientific literacy test instrument conducted at the beginning and at the end of learning (pretest and posttest). The results of the study indicate that the learning media is categorized as very feasible, very practical, and effective with n-gain scores that show high criteria. Based on the results of this study, the development of comic learning media based on Project Based Learning (PjBL) can be an alternative innovative media in improving the scientific literacy of eighth grade junior high school students.